PERANCANGAN GIRDER PADA FLEKSIBEL GANRTY CRANE KAPASITAS 1 TON - Rachmad Imbang Tritjahjono; Ramadhan Ramadhan; Destri Muliastri; Casiman Sukardi; Yun Gemilang (P3M Politeknik Negeri Indramayu, 2023)
Lifting and transporting equipment is one of the keys to carrying out work in the manufacturing and construction industries. Due to limited access, various obstacles must be overcome in some working areas. A ganrty crane is an alternative lifting equipment that has high flexibility. This article reports the research results on the girder’s main components. This component gets direct contact with loading when lifting and rigging work is carried out. This research method was conducted by comparing manual calculation models and CAE using the Solidworkss Simulation software. From these two methods, this study yielded 23.091 and 25.54MPa for manual calculations and the finite element method, respectively. Furthermore, in the finite element method with direct contact loading, a stress of 40.52MPa is obtained. From the three stress calculations, it can be concluded that the safety factor has exceeded the requirements set out in the standard. Furthermore, utilizing the Goodman model, mitigating the possibility of fatigue failure also indicates a safe condition. Based on recent research reports, a potential self-healing is not yet possible to be recognized well especially for metals having a grain size of micron.